2020
DOI: 10.18632/aging.202205
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of JAK1 associated with immune infiltration and poor prognosis in lung adenocarcinoma

Abstract: Janus kinase 1 (JAK1) is a member of the JAK family, which plays an essential and non-redundant role in tumorigenesis. However, the potential role of JAK1 in immune infiltration and prognosis of lung adenocarcinoma (LUAD) remains unclear. The mRNA expression and methylation level of JAK1 in LUAD were examined using the Oncomine and The Cancer Genome Atlas (TCGA) databases, respectively. The correlations between JAK1 expression and its methylation level and clinicopathological parameters were analyzed. The Kapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Moreover, in Part 1b/Groups A-1/A-2, 4 patients achieved a PR with no remarkable efficacy observed in any one tumor type treated with itacitinib plus pembrolizumab. In a database analysis study of lung adenocarcinoma transcriptome profiles, JAK1 expression was positively correlated with immune-cell infiltration, suggesting a potential role of JAK1 in the immune response ( 25 ). In a noncancer but immune-related setting, JAK1 signaling has been implicated in the immune response in acute GVHD, and treatment with itacitinib demonstrated clinical benefit in a phase I study ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in Part 1b/Groups A-1/A-2, 4 patients achieved a PR with no remarkable efficacy observed in any one tumor type treated with itacitinib plus pembrolizumab. In a database analysis study of lung adenocarcinoma transcriptome profiles, JAK1 expression was positively correlated with immune-cell infiltration, suggesting a potential role of JAK1 in the immune response ( 25 ). In a noncancer but immune-related setting, JAK1 signaling has been implicated in the immune response in acute GVHD, and treatment with itacitinib demonstrated clinical benefit in a phase I study ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that abnormal activation of the IL-6/STAT3 pathway could induce the expression of PD-L1, enhance tumor cell proliferation, and inhibit tumor cell apoptosis in NSCLC ( 30 , 31 ). In addition, Cai et al reported that decreased expression of JAK1 was associated with immune infiltration and a poor prognosis in LUAD tissues ( 32 ). While the specific regulatory mechanism of RHEX involved in JAK-related signaling pathways needs to be verified through more detailed experiments, the low expression group was mainly enriched in multiple gene sets with well-established roles in NSCLC development, including G2M_CHECKPOINT, MYC_TARGETS_V1/V2, E2F_TARGETS, DNA_REPAIR, MTORC1_SIGNALING, and GLYCOLYSIS.…”
Section: Discussionmentioning
confidence: 99%
“…Matrigel (25 µl Matrigel was diluted in 25 µl serum-free medium and cultured at 37˚C for 2 h)-coated Transwell chambers (BD Biosciences) were used for cell invasion assessment. A total of 1x10 5 LUAD cells resuspended in FBS-free medium were placed into the top chamber, while 600 µl of culture medium containing 15% FBS were added into the bottom chamber. Following incubation at 37˚C for 48 h, cells on the top of the filter were removed using cotton swabs, and cells on the bottom were fixed in 4% paraformaldehyde and then stained with 1% crystal violet (Beijing Solarbio Science & Technology Co., Ltd.) for 10 min at room temperature.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…The incidence of LUAD has increased in recent years, with the 5-year survival rate value as low as 15% (2). A number of genes have been reported to be dysregulated and to be involved in LUAD progression; however, the mechanisms underlying the occurrence and development of LUAD remain largely unknown (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%